ANGPTL2 promotes tumor metastasis in hepatocellular carcinoma. Issue 2 (February 2015) - Gao, Lin; Ge, Chao; Fang, Tao; Zhao, Fangyu; Chen, Taoyang; Yao, Ming; Li, Jinjun; Li, Hong
Abstract Background and Aim Angiopoietin‐like protein 2 (ANGPTL2) plays various roles in metabolism, vascular biology, inflammation, and tumor metastasis, but little is known about its function in human hepatocellular carcinoma (HCC) metastasis. This study aimed to further explore the function of ANGPTL2 on migration and invasion of liver cancer cells. Methods Quantitative real‐time polymerase chain reaction, Western blotting, immunohistochemistry, transwell migration, and invasion assays were performed to clarify the function of ANGPTL2 in the regulation of cell migration and invasion in human HCC. Results In HCC patients, ANGPTL2 expression was higher in HCC tissues compared with matched noncancerous liver tissues. And the ANGPTL2 levels of HCC tissues positively correlated with intrahepatic metastasis in HCC patients. Overexpression of ANGPTL2 significantly increased migration and invasion of HCC cells in vitro, and promoted intrahepatic and distal pulmonary metastasis in vivo, while knockdown of endogenous ANGPTL2 resulted in a reduced migration and invasion in vitro. Colony formation assay and 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay showed ANGPTL2 did not affect cell proliferation in vitro, whereas overexpression of ANGPTL2 promoted tumor formation in xenograft animal model. Conclusions Our findings show that ANGPTL2 drives human HCC metastasis and provides a potential therapeutic target for HCC treatment.